1991
DOI: 10.1161/01.hyp.17.6.1177
|View full text |Cite
|
Sign up to set email alerts
|

Lateral parabrachial nucleus and angiotensin II-induced hypertension.

Abstract: The objective of this study was to determine if ablation of the lateral parabrachial nucleus (LPBN) would prevent angiotensin II-induced hypertension in rats. Thirteen male SpragueDawley rats were studied. Bilateral electrolytic lesions in the LPBN were produced in six rats; the remaining seven rats were subjected to sham lesion surgery only. All rats were instrumented with vascular catheters and housed in metabolism cages. Daily measurements during the 16-day protocol included arterial pressure, heart rate, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…In addition, the LPBN has also been described as playing an integrative role in relaying baroreceptor information to forebrain regions, and bilateral ablation of the LPBN in rats has also prevented the development of sustained Ang II-induced hypertension. 22 Although further investigation is required, these data suggest that neurons located within brain stem regions and in the LPBN may play a role in regulating acute but not chronic Ang II-induced hypertension via an ascending baroreceptive pathway.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the LPBN has also been described as playing an integrative role in relaying baroreceptor information to forebrain regions, and bilateral ablation of the LPBN in rats has also prevented the development of sustained Ang II-induced hypertension. 22 Although further investigation is required, these data suggest that neurons located within brain stem regions and in the LPBN may play a role in regulating acute but not chronic Ang II-induced hypertension via an ascending baroreceptive pathway.…”
Section: Discussionmentioning
confidence: 93%
“…19 We have previously shown that the fluorescein isothiocyanate-labeled AS-ODN was taken up into the tissue around the third or lateral ventricle by intracerebroventricular injection 15 and that AS-ODN-AT 1 R decreased brain angiotensin receptors by use of membrane binding and autoradiographic analysis. 20 Other nuclei of the brain such as the lateral parabrachial nucleus 21 and the area postrema 22 have been reported to be important in Ang II-induced hypertensive rats. Therefore, the brain stem as a site of action cannot be ruled out because the AS-ODN injected in the cerebral ventricle may not have reached brain stem sites in sufficient amounts.…”
Section: Kagiyama Et Al Central Ras Inhibition In Chronic 2k1c 373mentioning
confidence: 99%
“…Arguments are based on the elimination of the hypertensive effect of Ang II by ablation of area postrema 3 or lateral parabrachial nucleus. 4 Furthermore, the hypertensive effect of subpressor doses of Ang II can be inhibited by central sympathoinhibitors, 5 ganglionic blockers, 6 nonselective ␣-blockade, 7 or renal denervation, 8 supporting a neurogenic pressor mechanism.The role of the brain RAS in the central control of cardiovascular homeostasis and pathophysiology is well documented. 9 Complementing and interacting with the endocrine RAS, the brain RAS is postulated to contribute to the pathology of hypertension and cardiovascular diseases.…”
mentioning
confidence: 99%
“…Arguments are based on the elimination of the hypertensive effect of Ang II by ablation of area postrema 3 or lateral parabrachial nucleus. 4 Furthermore, the hypertensive effect of subpressor doses of Ang II can be inhibited by central sympathoinhibitors, 5 ganglionic blockers, 6 nonselective ␣-blockade, 7 or renal denervation, 8 supporting a neurogenic pressor mechanism.…”
mentioning
confidence: 99%